Synergistic effects of heat and antibiotics on Pseudomonas aeruginosa biofilms. Issue 10 (26th November 2017) - Ricker, Erica B.; Nuxoll, Eric
Abstract: Upon formation of a biofilm, bacteria undergo several changes that prevent eradication with antimicrobials alone. Due to this resistance, the standard of care for infected medical implants is explantation of the infected implant and surrounding tissue, followed by eventual reimplantation of a replacement device. Recent studies have demonstrated the efficacy of heat shock for biofilm eradication. To minimize the heat required for in situ biofilm eradication, this study investigated the hypothesis that antibiotics, while ineffective by themselves, may substantially increase heat shock efficacy. The combined effect of heat and antibiotics on Pseudomonas aeruginosa biofilms was quantified via heat shock in combination with ciprofloxacin, tobramycin, or erythromycin at multiple concentrations. Combined treatments had synergistic effects for all antibiotics for heat shock conditions of 60°C for 5 min to 70°C for 1 min, indicating an alternative to surgical explantation.